Hotel Purchasing sebagai Fungsi Pengendalian Biaya dan Peningkatan Profit - Budi Hermawan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2003)
Purchasing is a series of activities resulting in the selection and acquisition of desired commodities services. The purchasing function is extremely important. Any money that is saved during the purchasing process goes directly to the bottom line. Purchasing in the hospitality industries operation is a routine activity to purchase the good. Purchasing is an essential activity because controlling the cost of operation could be started from purchase. The wrong purchase causes inefficient operation, and the business could be lost. Managers of any business venture must understand the importance of controlling the purchasing function. Efficiently and effectiveness in purchasing should be saved cost for product. It could be to support generating profit in operation. The difficulty of generating a profit is only one of the reasons why the purchasing functions so pertinent. The purchasing could be efficient and effective if its activity base on 6 (six) objective of purchase, as follows: right product, the right price, right quality, right quantity, right time and the right supplier. Many managers in a business have an image that the profit only gets from generating sales, to increase the profit, the manager must be increase sales of the product. However, purchasing could be generating profit most easily and efficiently more than generating profit from sales. Generating profit in operation could be get from purchasing control. In this manner, the business could increase the power competitive by cost control from purchase